Adamantanes for the treatment of neurodegenerative diseases in the presence of SARS-CoV-2 - Butterworth, Roger F. (Frontiers in Neuroscience, 2023)
Advent of the acute respiratory coronavirus SARS-CoV-2 has resulted in the search for novel antiviral agents and in the repurposing of existing agents with demonstrated efficacy against other known coronaviruses in the search for an agent with antiviral activity for use during the COVID-19 pandemic. Adamantanes including amantadine, rimantadine, and memantine have well-established benefit in the treatment of neurodegenerative diseases including Parkinson’s disease (PD), Alzheimer’s disease (AD) and fatigue related to Multiple sclerosis (MS) all of which are known comorbidities related to COVID-19 Moreover, results of basic pharmacological studies both in vitro and in vivo reveal that amantadine has the potential to inhibit SARS-CoV-2 via down-regulation of host-cell proteases resulting in impaired viral genome release into the host cell and via amantadine’s property as an NMDA receptor antagonist resulting in the prevention of the acute lung injury and respiratory distress that is characteristic of COVID-19. Cases suggestive of COVID-19 prophylaxis have been reported in patients with PD or MS or severe cognitive impairment treated in all cases for several months with an adamantane [amantadine or memantine] who were subsequently infected with SARS-CoV-2 confirmed by RT-PCR, and, in all cases, no signs of infectious disease were encountered. Amantadine is effective for the treatment of fatigue in MS and for the neurological complications of Traumatic Brain Injury (TBI).